Transuretral Resection of Prostate adenoma.: 100 cases - Gayol Collete, Mario; Pereyra Bonasso, Jorge; Viola Peluffo, Julio; García Guido, Luis (Cirugía del Uruguay, 1981)
Report o'f the author's experience in 100 T. U. R. of benign prostate hyperplasia. ResuJ'ts are comparable to those generally found in literature on this subject